Tumor microenvironment parameters as a predictor of the duration of clinical effectiveness of immunotargeted therapy in advanced or metastatic endometrial cancer: A pilot multicenter observational study - A. A. Maltseva; A. Yu. Kalinchuk; N. V. Krakhmal; N. M. Chernorubashkina; E. S. Martynova; R. A. Zukov; A. A. Gofman; A. B. Villert; O. N. Churuksaeva; L. A. Kolomiets; L. A. Tashireva (Опухоли женской репродуктивной системы)
Background. The inclusion of lenvatinib in the immunotherapy regimen for patients with MSS/pMMR endometrial cancer (EC) is due to its ability to modulate the tumor microenvironment, which allows the use of pembrolizumab in low-immunogenic tumors. However, only 30 % of patients with advanced or metastatic EC have a clinical response when treated with pembrolizumab and lenvatinib. In this regard, there is an obvious need to identify biomarkers that allow accurate selection of candidates for this type of therapy.Aim. To determine the predictive value of subpopulations of lymphocytes and macrophages, their expression of PD-1, expression of estrogen receptors, as well as vessel density in immunotargeted therapy for advanced or metastatic EC.Materials and methods. An open-label non-randomized observational association study was performed, involving a total of 22 patients with advanced or metastatic MSS/pMMR EC treated with pembrolizumab and lenvatinib. Duration of clinical effectiveness was used as a parameter to stratify patients. Using TSA-associated multiplex immunofluorescence, the proportions of CD8+ T lymphocytes, CD20+ B lymphocytes, FoxP3+ T regulatory lymphocytes and CD163+macrophages in tumor samples before the start of immunotargeted therapy were analyzed.Results. Three microenvironmental parameters were found to be associated with duration of clinical efficacy: the proportion of CD20+ B cells, the proportion of FoxP3+ T regulatory lymphocytes, and the ratio of CD8+/CD20+ lymphocytes in the tumor microenvironment. However, the CD8+/CD20+ lymphocyte ratio had the greatest predictive value; a value below 3.219 was associated with long clinical efficacy in patients with advanced or metastatic EC.Conclusion. The ratio of cytotoxic and B-lymphocytes in the microenvironment is a reliable predictor marker of the duration of the period of clinical effectiveness of immunotargeting therapy in advanced or metastatic EC.